Behavioural Drivers of Financial Well-Being Among Private School Teachers: Reconsidering the Role of Saving Habits - Jul Aidil Fadli; Tegar Satya Putra (Yayasan Sinergi Kawula Muda, 2026)
This study examines the relationships among financial literacy, risk tolerance, future time perspective, saving habits, and financial well-being. This empirical model addresses limited evidence in research on teachers' context related to financial well-being. This study used a quantitative approach, employing a questionnaire administered to private school teachers in Jakarta. The data were collected from 160 non-certified private school teachers who were aged 23 to 55. Partial Least Squares - Structural Equation Modelling (PLS-SEM) were used to analysed the data. The findings show that future time perspective is the strongest predictor, with positive effects on both financial well-being and saving habits. Saving habits also enhance financial well-being, suggesting that routine saving behaviour plays an important role in strengthening teachers' perceived financial security. Financial literacy does not directly improve financial well-being, but it significantly promotes saving habits, indicating that financial knowledge becomes more meaningful when translated into disciplined financial behaviour. Risk tolerance shows no significant direct and indirect effect on financial well-being, implying that willingness to take financial risks may not necessarily support well-being through saving behaviour. Then, saving habits were not proven to be a mediator between financial literacy, risk tolerance, future time perspective, and financial well-being. This is because saving is a necessity in the context of urban workers in big cities, so financial behaviour is not always initiated by intention, but rather by conditions that require them to survive. This study highlights the importance of future-oriented thinking and consistent saving habits as key behavioural foundations of financial well-being.